Activated macrophages as a feeder layer for growth of resident cardiac progenitor cells - Sepúlveda, Diana Elizabeth (2014)
The adult heart contains a population of cardiac progenitor cells (CPCs). Growing and collecting an adequate number of CPCs demands complex culture media containing growth factors. Since activated macrophages secrete many growth factors, we investigated if activated isolated heart cells seeded on a feeder layer of activated peritoneal macrophages (PM) could result in CPCs and if these, in turn, could exert cardioprotection in rats with myocardial infarction (MI). Heart cells of inbred Wistar rats were isolated by collagenase digestion and cultured on PM obtained 72 h after intraperitoneal injection of 12 ml thioglycollate. Cells (1 × 106) exhibiting CPC phenotype (immunohistochemistry) were injected in the periphery of rat MI 10 min after coronary artery occlusion. Control rats received vehicle. Three weeks later, left ventricular (LV) function (echocardiogram) was assessed, animals were euthanized and the hearts removed for histological studies. Five to six days after seeding heart cells on PM, spherical clusters composed of small bright and spherical cells expressing mostly c-Kit and Sca-1 antigens were apparent. After explant, those clusters developed cobblestone-like monolayers that expressed smooth muscle actin and sarcomeric actin and were successfully transferred for more than ten passages. When injected in the MI periphery, many of them survived at 21 days after coronary ligature, improved LV ejection fraction and decreased scar size as compared with control rats. CPC-derived cells with cardiocyte and smooth muscle phenotypes can be successfully grown on a feeder layer of activated syngeneic PM. These cells decreased scar size and improved heart function in rats with MI.